مظاهر تكريم المرأة فى الإسلام - دراسة تحليلية في ضوء حقوق المرأة: Manifestations of Woman’s Dignity in Islam An Analytical Study in the light of Woman’s rights - Dr Zainab Sadiq; Dr Hafiz Moazzum Shah (Al Manhal Research Journal, 2023)
This analytical study examines the manifestations of woman's dignity in Islam, specifically in relation to woman's rights. Islam upholds the value and significance of women, emphasizing their dignity as individuals deserving respect, equity, and justice. This study investigates various aspects of woman's dignity in Islam, considering their social, economic, and legal rights. Starting with an overview of the Quran and Hadith, the primary sources of Islamic teachings, the study explores the principles and values that promote woman's dignity. It delves into themes such as equality, education, marriage, employment, and the role of women in society, analyzing the rights and protections accorded to women in each domain.It draws upon historical examples and narratives to underscore Islam's recognition of women's dignity through their participation in various spheres including education, governance, and community work. In addition, this study also addresses some misconceptions and misunderstandings surrounding women's rights in Islam. By exploring the teachings in their proper context. Overall, this analytical study aims to shed light on the manifestations of woman's dignity in Islam, providing a comprehensive understanding of the rights and empowerment afforded to women. By examining Islamic teachings and historical precedents, it seeks to contribute to the ongoing discourse on women's rights, promoting a more nuanced understanding of Islam's stance on gender equality and the dignity of women.